2012
DOI: 10.1007/s10802-012-9610-2
|View full text |Cite
|
Sign up to set email alerts
|

Peer Rejection and Friendships in Children with Attention-Deficit/Hyperactivity Disorder: Contributions to Long-Term Outcomes

Abstract: Even after evidence-based treatment, Attention-Deficit/Hyperactivity Disorder (ADHD) is associated with poor long-term outcomes. These outcomes may be partly explained by difficulties in peer functioning, which are common among children with ADHD and which do not respond optimally to standard ADHD treatments. We examined whether peer rejection and lack of dyadic friendships experienced by children with ADHD after treatment contribute to long-term emotional and behavioral problems and global impairment, and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
184
0
22

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(213 citation statements)
references
References 77 publications
(112 reference statements)
7
184
0
22
Order By: Relevance
“…31 Consistent with previous research, 32 peer problems were elevated in our ADHD group, with large effect sizes observed. Peer problems in children who have ADHD do not generally respond to ADHD treatment, 33 and require specific intervention.…”
Section: Discussionmentioning
confidence: 99%
“…31 Consistent with previous research, 32 peer problems were elevated in our ADHD group, with large effect sizes observed. Peer problems in children who have ADHD do not generally respond to ADHD treatment, 33 and require specific intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in samples of children with externalizing behavior or ADHD have found that having at least one good friend buffers the negative effects of peer rejection on maladjustment [34,35] and receipt of victimization [36]. However, other work involving an ADHD sample found that only peer rejection, and not friendship, contributed to negative outcomes such as depression 6 and 8 years later [37]. The mixed results may be attributable to the fact that these studies have focused on the quantity of friends as a predictor, and have not considered friendship quality, stability, or the characteristics of the friends.…”
Section: Implications Of Peer Problems For Maladjustmentmentioning
confidence: 99%
“…Moreover, if there is only one computer available in a classroom, students often have to share this computer. It is reasonable to consider that students with ADHD might not have easy accessibility to the one computer that is shared by the whole class, as a result of a lack of self-esteem due to past experiences of being socially excluded by their classmates (33,34).…”
Section: Discussionmentioning
confidence: 99%